Moderating effect of demographic and business characteristics on performance of women owned small enterprises: empirical evidence from India - Vasan, Mohan (Serbian Journal of Management, 2020)
This study aims to explore the moderating effect of demographic and business characteristics on the performance of women-owned small enterprises. The theoretical and existing literature supports the moderating effect of demographic and business characteristics on business performance. The study adopted the descriptive research method. The primary data was gathered from 340 women owners of small enterprises and surveyed through a structured questionnaire. The Liner multiple regression was used to test the hypotheses. The findings of the study reveal that demographic characteristics such as father’s occupation, education, and experience were significantly associated with business performance. Hence, age and marital status were not significantly associated with the business performance of women-owned small enterprises. Business characteristics such as the age of business, location of the business, and type of business were significantly associated with business performance.